2017
DOI: 10.1111/cdev.12890
|View full text |Cite
|
Sign up to set email alerts
|

If You're Happy and You Know It: Positive Moods Reduce Age‐Related Differences in False Memory

Abstract: When tested in the Deese-Roediger-McDermott paradigm, children typically exhibit fewer false memories than do adolescents or adults. Here, participants' moods and the valence of word lists were manipulated to explore the mechanism responsible for this developmental reversal in memory performance. Children (7- to 8-year-olds), adolescents (11- to 12-year-olds), and young adults (18- to 22-year-olds; N = 270) were assigned to one of three induced mood conditions and were presented with emotional word lists. In n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…When this mechanism is taken into account in studies examining PTSD, depression, and false memories, we suggest that individuals with either PTSD or depression rapidly and automatically activate associations when they are confronted with pathology-related emotional experiences. The consequence of this automatic activation is that false memories for emotional material are more likely to be generated (also see Zhang et al, in press ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When this mechanism is taken into account in studies examining PTSD, depression, and false memories, we suggest that individuals with either PTSD or depression rapidly and automatically activate associations when they are confronted with pathology-related emotional experiences. The consequence of this automatic activation is that false memories for emotional material are more likely to be generated (also see Zhang et al, in press ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, whereas AAT can account for the fact that both semantically and phonologically related items can increase false memory rates, FTT cannot (see Finley, Sungkhasettee, Roediger, & Balota, 2017 ). Third, and something that is critical to what we are discussing in the current article, recent evidence has demonstrated that mood-congruent false memories are better explained by AAT than FTT particularly for moods that lead to increased automatic processing of information ( Zhang, Gross, & Hayne, in press ).…”
Section: Associative Activationmentioning
confidence: 95%
“…Among the 13-year-olds, accuracy was higher for negative than positive words, while in the younger group, accuracy was unrelated to word valence. Another study on word recall (Zhang et al, 2018) showed no age-related changes: Negative words were recalled better than positive words in two age groups (mean age 7.5 and 11.4 years, respectively).…”
Section: Review 1: Valence Effects In Word Processingmentioning
confidence: 92%
“…All participants completed a practice session to familiarize themselves with the DRM procedure before they were asked to watch a video clip that had a positive, negative, or neutral valence. To ensure that the to-be-used video clips would effectively induce the relevant mood states, we asked independent groups of 18- to 21-year-olds ( N = 11; 6 female) and 60- to 74-year-olds ( N = 11; 5 female) to watch three negative (i.e., sad), three positive (i.e., happy), and two neutral video clips used in previous studies (see Schaefer, Nils, Sanchez, & Philippot, 2010; Zhang, Gross, & Hayne, 2018). For each clip, participants were asked to use a 9-point graphic scale (1 = sad frowning face; 9 = happy smiling face) to rate how sad or happy that clip made them feel.…”
Section: Methodsmentioning
confidence: 99%
“…states, we asked independent groups of 18-to 21-year-olds (N ϭ 11; 6 female) and 60-to 74-year-olds (N ϭ 11; 5 female) to watch three negative (i.e., sad), three positive (i.e., happy), and two neutral video clips used in previous studies (see Schaefer, Nils, Sanchez, & Philippot, 2010;Zhang, Gross, & Hayne, 2018). For each clip, participants were asked to use a 9-point graphic scale (1 ϭ sad frowning face; 9 ϭ happy smiling face) to rate how sad or happy that clip made them feel.…”
Section: Materials and Proceduresmentioning
confidence: 99%